2023
DOI: 10.1007/s12011-023-03612-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Iodine Status of Lactating Women and Infants in Shanghai, China

Abstract: There is a risk of iodine de ciency in pregnant women in China. However, currently, little research is available on the iodine status of lactating women and infants. This study aimed to evaluate the iodine status of lactating women and their infants and explore the relationship between breast milk iodine concentration (BMIC) and urinary iodine concentration (UIC). 257 lactating women and their infants were recruited from the Shanghai Sixth People's Hospital East campus between May 2018 and May 2019. BMIC and U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…We found that children, lactating women, and weaning women all had a sufficient iodine status according to the WHO criteria, with median (p25-p75) UICs of 152.1 µg/L (75.8-268.3 µg/L), 121.3 µg/L (68.1-206.4 g/L), and 123.4 (58.4-227.2 g/L), respectively. Similar results were also reported in a smallscale study conducted in Shanghai among 257 lactating women and their infants between May 2018 and May 2019 [21]. The median (p25-p75) UIC of lactating women in that study was 110.0 µg/L (65.8-171.4 µg/L), while the median (p25-p75) UIC of infants was 212.7 µg/L (142.1-320.6 µg/L), both indicating iodine sufficiency [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that children, lactating women, and weaning women all had a sufficient iodine status according to the WHO criteria, with median (p25-p75) UICs of 152.1 µg/L (75.8-268.3 µg/L), 121.3 µg/L (68.1-206.4 g/L), and 123.4 (58.4-227.2 g/L), respectively. Similar results were also reported in a smallscale study conducted in Shanghai among 257 lactating women and their infants between May 2018 and May 2019 [21]. The median (p25-p75) UIC of lactating women in that study was 110.0 µg/L (65.8-171.4 µg/L), while the median (p25-p75) UIC of infants was 212.7 µg/L (142.1-320.6 µg/L), both indicating iodine sufficiency [21].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also reported in a smallscale study conducted in Shanghai among 257 lactating women and their infants between May 2018 and May 2019 [21]. The median (p25-p75) UIC of lactating women in that study was 110.0 µg/L (65.8-171.4 µg/L), while the median (p25-p75) UIC of infants was 212.7 µg/L (142.1-320.6 µg/L), both indicating iodine sufficiency [21]. A Norwegian study involving toddlers aged 18 months found a median (p25-p75) UIC of 129 µg/L (81-190 µg/L) [30], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our result was in line with previous data derived from a larger sample size of 2400 pregnant women in Shanghai, which showed that the proportion of iodine deficiency was 48% ( 11 ). Apparently, the phenomenon of iodine deficiency was widespread among pregnant women in Shanghai and most of them were in a situation of mild iodine deficiency ( 12 ). Pregnant women were vulnerable to iodine deficiency.…”
Section: Discussionmentioning
confidence: 99%